Synthesis And Imidization Of Disuccinamic Acid As Polyvinyl Alcohol-Composite Polymer - Aiube, Zakaria H.; Matty, Fadhel S.; Al-zaidi, Hiba A. Ghani (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two arylenedisuccinamic acids, namely 1,4-phenylene-disuccinamic acid and 4,4’biphenyl-disuccinamic acid were prepared from the reaction of two moles of succinic anhydride with one mole of 1,4-phenylenediamine dihydrochloride and beinzidine respectively.Dehydration of arylenedisuccinamic acid in the pressence of polyvinyl alcohol (PVA) and catalytic amount of concentrated.H2SO4,gives N,N’-arylenedisuccinimidesPVAcomposite polymers. Dehydration of arylenedisuccinamic acid (without PVA) in the pressence of catalytic amount of conc. H2SO4 gives N,N’-arylenedisuccinimides. Arylenedisuccinamic acid and arylenedisuccinimides characterized by CHN-analysis,FT.IR and 1H,C13-NMR.Spectral analysis